The relationship between nutritional status and preconceptional anemia in premarital women: A cecondary data analysis - Winarsih Nur Ambarwati; Faiza Arvianabilla; Rohani Mamat (Universitas Aisyiyah Yogyakarta, 2025)
Background: Anemia is a major public health issue in Indonesia, contributing to pregnancy complications and adverse maternal and infant outcomes. However, limited research has explored preconceptional anemia among premarital women. Objective: To determine the prevalence of anemia and to examine its relationship with nutritional status among premarital women. Methods: This cross-sectional study used secondary data from premarital health examinations conducted at a Community Health Center in Sukoharjo Regency, Central Java, throughout 2023. Six hundred women were included. The data were processed using descriptive statistics and the Chi-square test. Results: The prevalence of anemia among premarital women was 24.3%, which was higher than the national prevalence of 22.3%. Most participants were 20-35 years old and had normal body mass index (BMI). The highest prevalence of anemia occurred among women with normal BMI (30.4%), followed by underweight (27.3%) and overweight (17.3%). Statistical analysis indicated a significant association between nutritional status and anemia (p = 0.011). Conclusion: Nutritional status significantly affects anemia risk among premarital women. Normal BMI does not always reflect adequate micronutrient intake. Strengthening preconception services through routine anemia screening, iron folic acid supplementation, and nutrition education is crucial to improve maternal health outcomes.